BAGAIMANA PENGGUNAAN QUICK RESPONSE. INDONESIAN STANDARD (QRIS) MEMPENGARUHI PENGELOLAAN KEUANGAN UMKM DI JAWA BARAT? - Maharani Karnawijaya, Laksmi
The evolution of money has transitioned from barter systems to digital payments, with recent advancements in financial technology driving a global shift. While developed countries like the United Kingdom lead in digital payments, generating revenues of £6.6 billion annually, developing nations like Indonesia are rapidly adopting these technologies but still face challenges.